Antimicrobial Activities of Chemokines: Not Just a Side-Effect? - Wolf, Marlene; Moser, Bernhard (Frontiers in Immunology, 2012)
The large family of chemoattractant cytokines (chemokines) embraces multiple, in part unrelated functions that go well beyond chemotaxis. Undoubtedly, the control of immune cell migration (chemotaxis) is the single, unifying response mediated by all chemokines, which involves the sequential engagement of chemokine receptors on migrating target cells. However, numerous additional cellular responses are mediated by some (but not all) chemokines, including angiogenesis, tumour cell growth, T cell co-stimulation and control of HIV-1 infection. The recently described antimicrobial activity of several chemokines is of particular interest because antimicrobial peptides are thought to provide an essential first-line defence against invading microbes at the extremely large body surfaces of the skin, lungs and gastrointestinal-urinary tract. Here we summarize the current knowledge about chemokines with antimicrobial activity and discuss their potential contribution to the control of bacterial infections that may take place at the earliest stage of antimicrobial immunity. In the case of homeostatic chemokines with antimicrobial function, such as CXCL14, we propose an immune surveillance function in healthy epithelial tissues characterized by low-level exposure to environmental microbes. Inflammatory chemokines, i.e. chemokines that are produced in tissue cells in response to microbial antigens (such as pathogen-associated molecular patterns) may be more important in orchestrating the cellular arm in antimicrobial immunity.